PENGARUH LATIHAN GERAKAN DASAR BERPINDAH TEMPAT TERHADAP KELINCAHAN TENIS ATLET - MAHARANI FATIMA GANDASARI; Ahmad Atiq; Erna Yantiningsih; Ibrah Fastabiqi Bawana Mukti (Musamus Journal of Physical Education and Sport (MJPES), 2023)
Objectives. Agility is one of the indicators of an athlete's physical condition, where athletes can showcase their performance in an event or competition at their best. This study aims to assess the extent to which basic movement training in changing positions affects the agility of tennis athletes. Materials and methods. This experimental research utilizes a pretest and posttest group design with 9 subjects. The pretest is conducted initially before administering the treatment. The treatment given to the subjects includes lunges in changing positions, followed by one-legged hopping in changing positions, then two-legged jumping in changing positions, and concludes with a sprint. After the treatment, the subjects undergo an agility test using the Illinois agility run test. The researcher employs a T-test to analyze the data with a significance level of 5%. Results. The expected research results should demonstrate the impact of basic movement training in changing positions on the agility of tennis athletes, as evidenced by a calculated t-value of (25.764) > the critical t-value (2.306). Conclusion. Based on the findings of this research, it is recommended that coaches and trainers pay close attention to the agility of tennis athletes and periodically enhance it through basic movement training in changing positions to significantly improve agility among tennis athletes.